MORPHOMETRIC STUDY OF UPPER AND LOWER END OF HUMERUS FOR SEX IDENTIFICATION AND ITS CLINICAL SIGNIFICANCE IN ARTHROPLASTY - Pongen, Imennaro; Gupta, Chandni; Palimar, Vikram (Journal of Forensic Medicine and Toxicology, 2025)
Background: Various conditions required arthroplasty of humerus bone like osteoarthritis, Rheumatoid arthritis, and rotator cuff arthropathy etc. Identification of the sex of remains of the human body parts is also important for the forensic anthropologist. So, this study was conducted to measure the upper and lower ends of humerus to help in the reconstruction of the humerus as the joints are often the major region of damage during accidents and to differentiate male and female humerus which will help in identification of remains. Methods: A study is conducted on 95 dry humeri of unknown sex and various parameters are implemented to identify the gender of the humeri. The data is analyzed using SPSS software and an independent T-test was done to compare male and female and right and left parameters. Result: There were 17 parameters that are highly significant between males and females. There were only 3 parameters that were significant on the right and left sides as the P value was <0.05. Conclusion: The results of this study will help the orthopedic surgeon in constructing a prosthesis. Identification of sex of humerus bone is important and plays a vital role in the identification of human remains for the forensic anthropologists. Practical implications: The results of this study will help in making prosthesis during shoulder and elbow implantation surgeries. For forensic anthropologists in identification of gender by humerus bone.